The Relationship Between Lipid Profile and the Incidence of Relapsing Nephrotic Syndrome in Children - Utari Olivina Tarigan; Rosmayanti Syafriani Siregar; Syamsidah Lubis; Isti Ilmiati Fujiati; Melda Deliana; Cynthea Prima (Indonesian Journal of Global Health Research, 2025)
Nephrotic syndrome (NS) is one of the most common chronic kidney diseases in children, characterized by massive proteinuria, hypoalbuminemia, edema, and dyslipidemia. Relapse occurs in most cases and contributes to worsening the disease course. Dyslipidemia is suspected to influence relapse risk, but the specific relationship between lipid profile and relapsing NS remains unclear. Objective to analyze the association between total cholesterol, triglycerides, LDL, and HDL levels with relapse incidence in children with nephrotic syndrome. A retrospective study was conducted on 66 children aged 2–18 years with NS treated at H. Adam Malik General Hospital, Medan, in 2024. Subjects were divided into relapsing (n=54) and non-relapsing (n=12) groups. Data were obtained from medical records and analyzed using the Mann-Whitney test and Spearman correlation. Triglyceride (p=0.007), LDL (p=0.013), and HDL (p<0.001) levels differed significantly between the relapsing and non-relapsing groups. Total cholesterol showed no significant difference (p=0.164). The mean albumin level was significantly lower in the relapsing group (2.9 g/dL vs. 4.1 g/dL; p<0.001). A significant negative correlation was found between albumin and triglyceride levels (r=-0.326; p=0.008). Triglyceride, LDL, and HDL levels are significantly associated with relapse in pediatric nephrotic syndrome. Hypoalbuminemia is also an important risk factor. Lipid profile evaluation can serve as a useful indicator in monitoring and managing relapses.